Pregnant women fear and insecurity during labor as reasons for demanding early admission - Ferreira, Maria de Lourdes Silva Marques; Peron Giaxa, Thais Erika (Investigación y Educación en Enfermería, 2011)
Objective. To identify reasons why women look for early health care attention at the end of pregnancy. Methodology. Qualitative study based in socio-existential phenomenology proposed by Alfred Schütz. Nine pregnant women who consulted to the maternity service without being in real labor were interviewed. Results. The following analysis categories emerged: Having different symptoms or signals from the ones they had felt or been informed about, not being able to identify real labor, fear to fetal complications for being close to the probable labor date, feeling calmer when being seen by professionals of the institution, lack of problem solving by other services of the health institution, fearing out of hospital delivery, imitating real labor, looking for tranquility in the idealization of labor and modifying behaviors to guarantee attention. Conclusion. Women are insecure and fear because of a fragmented health care, where they do not perceive themselves linked to the prenatal control program anymore, and at the same time they don’t find the health care assistance they want.